2014
DOI: 10.1007/s00449-014-1322-2
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Candida rugosa lipase onto an eco-friendly support in the presence of ionic liquid

Abstract: Candida rugosa lipase (CRL) was immobilized on an eco-friendly support poly(3-hydroxybutyrate-co-hydroxyvalerate) (PHBV), by physical adsorption, using different ionic liquids (ILs) as immobilization additives. This was to investigate the influence of cationic core ([C4mpy]Cl, [C4min]Cl), of anions ([C4min]Cl, [C4min]N(CN)2, [C4min]Tf2N), and of cation chain length ([C2min]Tf2N, [C4min]Tf2N) in the immobilization process. The immobilized biocatalysts (IB) were characterized with respect to the morphological, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The group of signals at 1151 cm −1 , 1073 cm −1 and 1037 cm −1 are associated with the presence of C-O-C bonds in the protein structure [ 45 ]. In addition, of note are two signals below 1000 cm −1 : at 576 cm −1 a band of N-H stretching vibrations, and at 531 cm −1 a band of scissor vibrations of the C-C bonds forming the skeleton of the enzyme structure [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The group of signals at 1151 cm −1 , 1073 cm −1 and 1037 cm −1 are associated with the presence of C-O-C bonds in the protein structure [ 45 ]. In addition, of note are two signals below 1000 cm −1 : at 576 cm −1 a band of N-H stretching vibrations, and at 531 cm −1 a band of scissor vibrations of the C-C bonds forming the skeleton of the enzyme structure [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability of the immobilized biocatalysts was determined by incubating the samples at temperatures from 55 to 65 °C in water (0.1 mol L −1 phosphate buffer, pH 7.0) for 4 h. Thus, in different time periods, samples were removed, immediately cooled and used to determine activity according to Cabrera‐Padilla et al, with modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Although they have some disadvantages compared with AIL (lower conductivity and stability), LIP have qualities that overcome these limitations, such as methods of synthesis and purification which are simple, good biodegradability, low toxicity, and low cost, awakening the largest industrial interest . Several research studies have confirmed that ionic liquids are suitable media for enzyme catalysis; however, most found in the literature are using aprotic ionic liquids with only some using protic ionic liquids …”
Section: Introductionmentioning
confidence: 99%
“…The second method is easy, cheap, and allows simple recycling of the support when the enzyme is no more active. However, there is a possibility of enzymatic desorption 38,39 . Badgujar et al 9 .…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a possibility of enzymatic desorption. 38,39 Badgujar et al 9 also obtained activation of the enzyme (400%) after immobilization in PLA-CH-PVA film.…”
Section: Lipase Immobilization and Organic Reactionmentioning
confidence: 95%